Karl Marx’s Criticism on Religion - Juhansar Andi Latief (Al-Ulum, 2011)
This article discusses about the uniqueness of religion among other academic disciplines. Religion is almost exclusively approached as an object of study. This paper presents a descriptive criticism of Islam in Marx's critique of religion. The study then found that Islam and Marxism is essentially a contradiction particularly striking in view of the unity-an. Marx, based on the philosophy of Marxism; man- made ​​religion and religion does not make the man. However, Muslims believe in the spiritual concept of the infinite in which Islam describes the man as the ground; land; ground, or it can be said that religion, in this case, God created man, not vice versa.